Lichen sclerosus - Jabłonowska, Olga; Woźniacka, Anna; Żebrowska, Agnieszka (Dermatology Review/Przegląd Dermatologiczny, 2021)
Lichen sclerosus is a chronic skin condition with extragenital and/or genital involvement. The disease may develop in women and men of any age, but most frequently affects postmenopausal women. The aetiology of lichen sclerosus remains unknown. Genetic, infectious, environmental, autoimmune, and hormonal factors are presumed to influence its development. In most cases, lesions are located in the anogenital area. It is associated with sexual morbidity and is associated with an increased risk of cancerogenesis. The first-line treatment of lichen sclerosus includes ultrapotent corticosteroid ointments. Topical calcineurin inhibitors are considered second choice treatment. In recalcitrant cases alternative treatment methods (phototherapy and photochemotherapy, oral retinoids, methotrexate, cyclosporine, photodynamic therapy, adipose-derived stem cells and platelet-rich plasma, surgical management) are used. Because of a possible 3–8% risk of malignant transformation of genital lichen sclerosus to squamous cell carcinoma, early diagnosis is required, and long-term follow-up is recommended.